THE PARADIGM OF DIGITAL PRIVACY IN INDONESIAN TAFSIR: A STUDY OF TAFSIR AL-AZHAR ON QS. AL-HUJURĀT (49): 12 IN THE AGE OF INFORMATION - Lum'ah, Diana Durrotul; Musafa'ah, Suqiyah; Mahbub, Muhammad Ihsan (Universitas Nurul Jadid, 2025)
Digital privacy has become a global concern amid the widespread personal data breaches, as reflected in regulations such as the European Union's General Data Protection Regulation (GDPR) and reports by Amnesty International. In the context of Indonesian Muslim society, Islamic ethical values have the potential to serve as a normative foundation in responding to digital privacy challenges. Surah al-Ḥujurāt: 12 which prohibits suspicion, tajassus (spying or snooping), and ghibah (backbiting or gossip) is highly relevant in today's digital world. This study aims to examine the paradigm of digital privacy through Buya Hamka’s interpretation of this verse in Tafsir al-Azhar, and to explore its contribution to the development of digital ethics grounded in Qur'anic values. Employing a qualitative interpretive paradigm, this research adopts a thematic and comparative tafsir approach. The object of study is the ethical and normative meaning of Surah al-Ḥujurāt: 12 in a contemporary context. The primary data source is Tafsir al-Azhar, which is analyzed in depth, while secondary sources include literature on digital ethics, privacy policies, and other tafsir work. The analysis technique used is content analysis with a normative-thematic approach to link the moral values of the Qur'an with digital phenomena. The findings show that Buya Hamka interprets the verse in a social-moral framework, going beyond legalistic dimensions. The concept of tabayyun (verification), which he emphasizes, emerges as a key principle for information verification and personal data protection. This research highlights the importance of reinterpreting classical tafsir as an ethical response to the advancement of information technology, and as a contribution of Islam to the global discourse on digital ethics.